Adoptees and behavior problems: A meta-analysis - Swinton, Jonathan J. (Kansas State University, 2011)
Adoption trends have shifted in the past two decades and as a result, could impact established assumptions about behavior problems among adopted children. A comprehensive meta-analysis was published in 2005 attempting to come to more definitive conclusions regarding adoption behavior and moderators of adoption behavior. However, the study used a sample from over a dozen countries over a 44 year span. This study is a meta-analysis that has replicated many of the questions investigated by the previous analysis with a much more recent 15 year sample of adoptees placed only within the United States. The results show that combined international and domestic adoptee samples, as well as separate international and domestic adoptee samples are more likely to have total, externalizing, and internalizing behavior problems than their non-adopted counterparts. In addition, age at time of assessment, gender of adoptees, and length of time spent with adoptive family may moderate some of the behavior problems experienced by adoptees. Pre-adoptive adversity, age at time of assessment, and study quality were not shown to have moderating influence on behavior of adoptees.
Keywords: Adoption; Adoption behavior; Adoption behavior problems; Behavior problems; Adoptee; Adoptee behavior; Behavioral Sciences (0602); Individual & Family Studies (0628); Social Research (0344)